Alumina-based corundum mullite hollow sphere with gradient structure and preparation method thereof
By grading homogenization and overmolding of high alumina bauxite, combined with high-temperature calcination in situ pore formation process, a gradient structure alumina-based corundum mullite hollow sphere was designed, solving the existing refractory hollow spheres with thermal shock resistance The problems of poor performance and high production cost achieve efficient and low-energy-consuming fire-resistant hollow sphere preparation.
Patent Information
- Application Number
- CN202411668354.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing refractory hollow spheres have poor thermal shock resistance during high-temperature use, high production energy consumption and high raw material costs, which limits their large-scale application in high-temperature industries.
A combined process of high-alumina bauxite grading homogenization, overmolding, and high-temperature calcination in situ pore formation was used to design alumina-based corundum mullite hollow spheres with gradient structure.
It realizes a refractory hollow ball with low thermal conductivity, good corrosion resistance, high operating temperature and excellent thermal shock resistance, which reduces production energy consumption and meets the requirements of large-scale production.
Smart Images

Figure CN119462098A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heat-insulating refractory materials, and particularly relates to a bauxite-based corundum-mullite hollow sphere with a gradient structure and a preparation method thereof. Background Art
[0002] Refractory hollow balls have the characteristics of low thermal conductivity, high load softening temperature, good corrosion resistance, and excellent high-temperature mechanical properties. They can not only be used as thermal insulation layers, but also as high-temperature layers in direct contact with flames. They are one of the most promising high-performance thermal insulation refractory raw materials. At present, the industrial preparation method of refractory hollow balls is relatively single, mainly prepared by hollow ball blowing, that is, high-purity oxides such as Al2O3 and ZrO2 are electrofused into molten liquids at above 2000°C and blown with compressed air. The hollow balls obtained by this method have high use temperatures, but the spherical shell structure is uniform and dense, and its thermal shock resistance is poor; at the same time, the production energy consumption is high and the raw material cost is high, which limits its large-scale application in high-temperature industries. With the gradual deepening of energy conservation and carbon reduction needs in high-temperature industries, there is an urgent need to develop refractory hollow balls with excellent high-temperature performance, which can meet industrial preparation and have a richer source of raw materials.
[0003] my country's high-alumina bauxite resource reserves rank among the top in the country, but the development and application are still unbalanced. Among them, high-grade Class I high-alumina bauxite is in short supply, while the medium and low-grade ores (Class II and Class III materials) with more abundant reserves are underdeveloped and have low resource utilization. Among the bauxite-based refractory raw materials, Class I high-alumina bauxite is in the corundum phase after high-temperature calcination, and has the characteristics of high temperature resistance and good corrosion resistance; Class II and Class III high-alumina bauxite clinkers are mainly mullite-high silica glass phase, which has slightly lower refractoriness and poor wear resistance, but has the characteristics of low thermal conductivity, low thermal expansion coefficient and good high-temperature mechanical properties. In recent years, it has become a consensus in the industry to develop high-performance and high-value-added thermal insulation refractory raw materials based on the advantages of high-alumina bauxite resources. Publication No. CN117964353A announced that low-thermal conductivity alumina-based mullite synthetic materials were successfully prepared by modifying SiO2 to optimize the performance of porous materials using low-grade high-alumina bauxite as the main raw material. Publication No. CN10643143A announced that a high-strength, closed-cell mullite material was prepared using high-alumina bauxite and silicon dioxide as the main raw materials. The refractory heat-insulating raw materials synthesized using medium and low-grade high-alumina bauxite are mainly mullite phases, and have the advantages of low thermal conductivity and good mechanical properties. However, this type of refractory raw material is difficult to take into account the performance of high temperature resistance and corrosion resistance, and is only suitable for insulation layers and working layers with lower temperatures. Therefore, it is necessary to explore a new preparation method, and use the characteristics of different grades of high-alumina bauxite to design the gradient structure and regulate the performance of heat-insulating refractory raw materials, which can greatly improve the use temperature and application range of alumina-based heat-insulating refractory materials, and provide technical support for energy saving and carbon reduction in high-temperature industries. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide an alumina-based corundum-mullite hollow sphere with a gradient structure and a preparation method thereof. The present invention designs a gradient structure of the refractory hollow sphere by combining a process of high-alumina bauxite grading and homogenization, coating molding, and high-temperature calcination in-situ pore formation, making full use of the physical properties of corundum and mullite to develop a refractory hollow sphere with low thermal conductivity, good corrosion resistance, high operating temperature, and excellent thermal shock resistance.
[0005] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure comprises the following steps: The first step is to beneficiate high-alumina bauxite, grade and homogenize it to obtain grade I, II and III high-alumina bauxite fine powder; The second step is to grind 45-65% of grade III high alumina, 33-53% of silica, and 1-4% of mixed additives into fine powder of ≤600 mesh, and add 2-4wt% of organic binder to the above raw materials and mix them evenly to obtain a mixed raw material; The third step is to granulate the mixed raw materials in a disc granulator to obtain spherical particles with a particle size of 0.2-0.9 mm; The fourth step is to use the spherical particles as cores, wrap them with grade II high-alumina bauxite under the rotation of a granulator, and wrap the outermost layer with grade I high-alumina bauxite to obtain a non-homogeneous spherical particle body with rich SiO2 inside; The fifth step is to fully dry the above-mentioned heterogeneous spherical particle body, place it in a high-temperature rotary kiln, and calcine it at 1550-1650° C. for 1-3 hours to finally obtain a corundum-mullite hollow sphere with a gradient structure.
[0006] Furthermore, the particle size of the first step high alumina bauxite fine powder is ≤200 mesh; the Al2O3 content of grade III high alumina bauxite is 42~52wt%, and the SiO2 content is 32~45wt%; the Al2O3 content of grade II high alumina bauxite is 53~68wt%, and the SiO2 content is 15~31wt%; the Al2O3 content of grade I high alumina bauxite is ≥69wt%, and the SiO2 content is ≤15wt%.
[0007] Furthermore, the SiO2 content in the second step silica is ≥99.56wt%, and the particle size of the silica raw material is ≤180 mesh.
[0008] Furthermore, the second step mixed additive is a mixture of one of lanthanum cerium carbonate, cerium carbonate, and lanthanum carbonate and SiC, and the particle size of the mixed additive is ≤200 mesh.
[0009] Furthermore, the mass ratio of lanthanum cerium carbonate, cerium carbonate or lanthanum carbonate to SiC in the mixed additive is 1-10:1.
[0010] Furthermore, the organic binder in the second step is one of polyvinyl alcohol, dextrin and corn starch.
[0011] Furthermore, in the fourth step, the mass of the grade II high-alumina bauxite is 25-35% of the spherical particles, and the mass of the grade I high-alumina bauxite is 10-15% of the spherical particles.
[0012] Furthermore, the alumina-based corundum-mullite hollow spheres prepared by the preparation method are formed in situ during the heating and calcining process, and the phase of the hollow sphere shell presents a gradient distribution structure, wherein the outer shell is mainly composed of the corundum phase, and the mullite phase gradually increases from the surface of the sphere shell to the inside.
[0013] Furthermore, the corundum phase accounts for 70% to 90% of the spherical shell surface of the alumina-based corundum-mullite hollow sphere.
[0014] Furthermore, the volume density of the alumina-based corundum mullite hollow sphere is 1.0-1.6 g / cm 3 The average shell thickness is 0.1~0.2mm.
[0015] Furthermore, the thermal conductivity of the alumina-based corundum-mullite hollow sphere is 0.3-1.0 W / (m·K), and the operating temperature is 1550-1650°C.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses resource-rich bauxite mineral as the main raw material, and utilizes the in-situ diffusion reaction of the prepared heterogeneous spherical particle body during the calcination process to form a hollow structure; the graded homogenization-coating molding-high-temperature calcination in-situ pore-forming process is used to prepare refractory hollow balls, which has high pore-forming efficiency and low energy consumption, and can meet the requirements of large-scale production.
[0017] 2. The present invention designs a gradient structure for the refractory hollow sphere based on the characteristics of different grades of high alumina. The outer layer of the hollow sphere shell is mainly composed of corundum phase, which ensures the corrosion resistance and high temperature resistance of the refractory raw materials; the inner layer of the sphere shell is cross-linked columnar mullite, which improves the mechanical properties and high-temperature volume stability of the refractory hollow sphere.
[0018] 3. The hollow sphere layer formed by the present invention has different crystal morphologies, which can cause crack deflection inside the hollow sphere, hinder the expansion of large cracks, and improve the thermal shock resistance of the refractory hollow sphere. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a microstructure diagram of the cross section of the alumina-based corundum-mullite hollow sphere with a gradient structure prepared in Example 1 of the present invention.
[0020] Figure 2 The microstructure and energy spectrum element distribution diagram of the cross section of the alumina-based corundum-mullite hollow sphere with gradient structure prepared in Example 2 of the present invention after resin curing. DETAILED DESCRIPTION
[0021] The technical solution and effects of the present invention are further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto. Example 1
[0022] This embodiment provides a method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure, comprising the following steps: The high-alumina bauxite is beneficiated, graded and homogenized to obtain grade I, II and III high-alumina bauxite fine powders; 60wt% of grade III high-alumina bauxite, 38wt% of silica and 2wt% of mixed additives are ground into fine powder of ≤600 mesh, and 4wt% of corn starch is added to the above raw materials and mixed evenly to obtain a mixed raw material; The mixed raw materials are granulated in a disc granulator to obtain spherical particles with a particle size of 0.2-0.6 mm; The spherical particles are used as cores, and are coated with 35wt% of grade II high-alumina based on the spherical particles under the rotation of a granulator, and the outermost layer is coated with 10wt% of grade I high-alumina to obtain a non-homogeneous spherical particle blank with rich SiO2 inside; The above-mentioned heterogeneous spherical particle body is fully dried, placed in a high-temperature rotary kiln, and calcined at 1600° C. for 3 hours to finally obtain a corundum-mullite hollow sphere with a gradient structure.
[0023] The high-alumina bauxite described in this embodiment is classified, homogenized and finely ground, and the raw material particle size is ≤200 mesh, wherein the Al2O3 content of the grade III high-alumina bauxite is 45wt%, and the SiO2 content is 39wt%; the Al2O3 content of the grade II high-alumina bauxite is 55wt%, and the SiO2 content is 30wt%; the Al2O3 content of the grade I high-alumina bauxite is 78wt%, and the SiO2 content is 8wt%. The SiO2 content in the silica is 99.65wt%, and the raw material particle size is ≤180 mesh. The mixed additives are lanthanum cerium carbonate and SiC, and according to the mass ratio, lanthanum cerium carbonate: SiC=3:1, and the raw material particle size is ≤200 mesh.
[0024] The technical indicators of the alumina-based corundum-mullite hollow spheres prepared in this embodiment are: the volume density of the hollow spheres is 1.25 g / cm 3The average shell thickness is 0.15mm. The content of corundum phase on the surface of the hollow sphere shell is 75.5%, and the inside of the shell is mullite-high silica glass phase. The thermal conductivity of the hollow sphere is 0.55 W / (m·K), and the operating temperature is ≥1600℃. Figure 1 The microstructure shown in the figure is prepared according to the steps of Example 1. Figure 1 It can be seen that the crystal morphology and phase composition of the hollow sphere shell are distributed in a gradient: the inner layer of the spherical shell is cross-linked columnar mullite, the middle layer of the spherical shell is a corundum-mullite composite structure, and the surface of the hollow sphere shell is mainly granular and flaky corundum. Example 2
[0025] This embodiment provides a method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure, comprising the following steps: The high-alumina bauxite is beneficiated, graded and homogenized to obtain grade I, II and III high-alumina bauxite fine powders; 55wt% of grade III high-alumina bauxite, 42wt% of silica and 3wt% of mixed additives are ground into fine powder of ≤600 mesh, and 4wt% of dextrin is added to the above raw materials and mixed evenly to obtain a mixed raw material; The mixed raw materials are granulated in a disc granulator to obtain spherical particles with a particle size of 0.3-0.8 mm; The spherical particles are used as cores, and are coated with 25wt% of grade II high-alumina based on the spherical particles under the rotation of a granulator, and the outermost layer is coated with 15wt% of grade I high-alumina to obtain a non-homogeneous spherical particle blank with rich SiO2 inside; The above-mentioned heterogeneous spherical particle body is fully dried, placed in a high-temperature rotary kiln, and calcined at 1650° C. for 2 hours to finally obtain a corundum-mullite hollow sphere with a gradient structure.
[0026] The high-alumina bauxite described in this embodiment is classified, homogenized and finely ground, and the raw material particle size is ≤200 mesh, wherein the Al2O3 content of grade III high-alumina bauxite is 43wt%, and the SiO2 content is 41wt%; the Al2O3 content of grade II high-alumina bauxite is 60wt%, and the SiO2 content is 26wt%; the Al2O3 content of grade I high-alumina bauxite is 85wt%, and the SiO2 content is 5.5wt%. The SiO2 content in the silica is 99.70wt%, and the raw material particle size is ≤180 mesh. The mixed additives are cerium carbonate and SiC, and according to the mass ratio, cerium carbonate: SiC=3.5:0.5, and the raw material particle size is ≤200 mesh.
[0027] The technical indicators of the alumina-based corundum-mullite hollow spheres prepared in this embodiment are: the volume density of the hollow spheres is 1.35 g / cm 3The average shell thickness is 0.20mm, the content of corundum phase on the surface of the hollow sphere shell is 80.5%, the inside of the shell is mullite-high silica glass phase, the thermal conductivity of the hollow sphere is 0.63W / (m·K), and the operating temperature is ≥1600℃. Figure 2 The microstructure diagram and energy spectrum diagram shown in the figure are prepared according to the steps of Example 2. Figure 2 It can be seen that the elements in the hollow sphere shell are distributed in a gradient manner, and the SiO2 element gradually increases from the surface of the shell to the inside. Example 3
[0028] This embodiment provides a method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure, comprising the following steps: The high-alumina bauxite is beneficiated, graded and homogenized to obtain grade I, II and III high-alumina fine powders; 45wt% of grade III high-alumina bauxite, 53wt% of silica and 2wt% of mixed additives are ground into fine powder of ≤600 mesh, and 3wt% of polyvinyl alcohol is added to the above raw materials and mixed evenly to obtain a mixed raw material.
[0029] The mixed raw materials are granulated in a disc granulator to obtain spherical particles with a particle size of 0.4-0.9 mm; The above-mentioned spherical particles are used as cores, and are coated with 25wt% of grade II high-alumina based on the spherical particles under the rotation of a granulator, and the outermost layer is coated with 15wt% of grade I high-alumina to obtain a non-homogeneous spherical particle blank with rich SiO2 inside; The above-mentioned non-homogeneous spherical particle body is fully dried, placed in a high-temperature rotary kiln, and calcined at 1550° C. for 3 hours to finally obtain a corundum-mullite hollow sphere with a gradient structure.
[0030] The high-alumina bauxite described in this embodiment is classified, homogenized and finely ground, and the raw material particle size is ≤200 mesh, wherein the Al2O3 content of the grade III high-alumina bauxite is 42wt%, and the SiO2 content is 43wt%; the Al2O3 content of the grade II high-alumina bauxite is 55wt%, and the SiO2 content is 30wt%; the Al2O3 content of the grade I high-alumina bauxite is 75wt%, and the SiO2 content is 10wt%. The SiO2 content in the silica is 99.70wt%, and the raw material particle size is ≤180 mesh. The mixed additives are lanthanum carbonate and SiC, and according to the mass ratio, lanthanum carbonate: SiC=3.5:0.5, and the raw material particle size is ≤200 mesh.
[0031] The technical indicators of the alumina-based corundum-mullite hollow spheres prepared in this embodiment are: the volume density of the hollow spheres is 1.10 g / cm 3The average shell thickness is 0.15mm, the content of corundum phase in the outer shell of the hollow sphere is 70.0%, and the inner shell is mullite-high silica glass phase. The thermal conductivity of the hollow sphere is 0.40W / (m·K), and the operating temperature is ≥1550℃.
[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure, characterized in that: The preparation method comprises the following steps: The first step is to beneficiate high-alumina bauxite, grade and homogenize it to obtain grade I, II and III high-alumina bauxite fine powder; The second step is to grind 45-65% of grade III high alumina, 33-53% of silica, and 1-4% of mixed additives into fine powder of ≤600 mesh, and add 2-4wt% of organic binder to the above raw materials and mix them evenly to obtain a mixed raw material; The third step is to granulate the mixed raw materials in a disc granulator to obtain spherical particles with a particle size of 0.2-0.9 mm; The fourth step is to use the spherical particles as cores, wrap them with grade II high-alumina bauxite under the rotation of a granulator, and wrap the outermost layer with grade I high-alumina bauxite to obtain a non-homogeneous spherical particle body with rich SiO2 inside; The fifth step is to fully dry the above-mentioned heterogeneous spherical particle body, place it in a high-temperature rotary kiln, and calcine it at 1550-1650° C. for 1-3 hours to finally obtain a corundum-mullite hollow sphere with a gradient structure.
2. The method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure according to claim 1, characterized in that: The particle size of the high-alumina bauxite fine powder in the first step is ≤200 mesh; the Al2O3 content in grade III high-alumina bauxite is 42~52wt%, and the SiO2 content is 32~45wt%; the Al2O3 content in grade II high-alumina bauxite is 53~68wt%, and the SiO2 content is 15~31wt%; the Al2O3 content in grade I high-alumina bauxite is ≥69wt%, and the SiO2 content is ≤15wt%.
3. The method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure according to claim 1, characterized in that: The second step mixed additive is a mixture of one of lanthanum cerium carbonate, cerium carbonate, and lanthanum carbonate and SiC, and the particle size of the mixed additive is ≤200 meshes.
4. The method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure according to claim 3, characterized in that: The mass ratio of lanthanum cerium carbonate, cerium carbonate or lanthanum carbonate to SiC in the mixed additive is 1-10:
1.
5. The method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure according to claim 1, characterized in that: In the second step, the organic binder is one of polyvinyl alcohol, dextrin and corn starch.
6. The method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure according to claim 1, characterized in that: In the fourth step, the mass of the grade II high-alumina bauxite is 25-35% of the spherical particles, and the mass of the grade I high-alumina bauxite is 10-15% of the spherical particles.
7. The method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure according to claim 1, characterized in that: The alumina-based corundum-mullite hollow spheres prepared by the preparation method are formed in situ during the heating and calcining process, and the phases of the hollow sphere shell present a gradient distribution structure, wherein the outer shell is mainly composed of the corundum phase, and the mullite phase gradually increases from the surface of the sphere shell to the inside.
8. The method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure according to claim 7, characterized in that: The corundum phase accounts for 70% to 90% of the spherical shell surface of the alumina-based corundum-mullite hollow sphere.
9. The method for preparing alumina-based corundum-mullite hollow spheres with a gradient structure according to claim 7, characterized in that: The volume density of the alumina-based corundum-mullite hollow sphere is 1.0-1.6 g / cm 3 The average shell thickness is 0.1~0.2mm.
10. The method for preparing alumina-based corundum-mullite hollow spheres with gradient structure according to claim 7, characterized in that: The thermal conductivity of the alumina-based corundum-mullite hollow sphere is 0.3-1.0 W / (m·K), and the use temperature is 1550-1650°C.
Citation Information
Patent Citations
Calcining process of synthesizing hollow silica alumina ball
CN101066875A
Gradient high-alumina refractory raw material ball and production method thereof
CN101597172A
Closed-pore bauxite based mullite material and preparing method thereof
CN106431434A
Lightweight high-strength aggregate prepared from rare earth coupled solid waste and preparation method thereof
CN117623739A
Preparation method of periclase-forsterite gradient composite hollow spheres
CN117819946A